PENERAPAN METODE BERNYANYI UNTUK PENGUASAAN KOSAKATA BAHASA ARAB PADA ANAK MADRASAH DINIYAH DI KAMPUNG TEGAL HEAS - Nissa Maisarah Azzahra; Usep Setiawan (Penerbit Widina, Widina Media Utama, 2023)
This study aims to master Arabic vocabulary in early childhood with singing techniques. Children of all ages basically love to listen, sing and learn with songs. Therefore, music is generally an important part of the teaching-learning process for young students. The results of the study showed that TPA students enjoyed learning Arabic by singing and more easily memorized the vocabulary taught by the teacher. Thus it can be concluded that singing techniques can improve vocabulary mastery of Arabic for early childhood, especially for Madrasah diniyah students in Tegal Heas village.